2021
DOI: 10.1055/s-0041-1731916
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Adrenal Suppression in Patients Having Sepsis in Indian Population and Impact of Corticosteroid Supplementation on Its Overall Survival

Abstract: Objective Our aim was to estimate the occurrence of adrenal suppression in critically ill patients with septic shock who have got admission in intensive care unit and to evaluate the effectiveness of hydrocortisone in these patients in relation to mortality of patient, development of septic shock, and effect on total leucocyte count. Methods Serum cortisol was measured in 120 patients with sepsis. Patients with decreased cortisol level were split in to two groups (group A and B). Group A received 50 mg of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…5 Another study found a co-occurrence rate of 36.6% (using serum cortisol). 6 In 2008, an international task force convened by the Society of Critical Care Medicine (SCCM) and the European Society of Intensive Care Medicine (ESICM) coined the phrase critical illness-related corticosteroid insufficiency (CIRCI) to more fully describe the impairment of the HPA axis during critical illness. 7 CIRCI was defined as inadequate cellular corticosteroid activity for the severity of the patient's critical illness.…”
Section: Introductionmentioning
confidence: 99%
“…5 Another study found a co-occurrence rate of 36.6% (using serum cortisol). 6 In 2008, an international task force convened by the Society of Critical Care Medicine (SCCM) and the European Society of Intensive Care Medicine (ESICM) coined the phrase critical illness-related corticosteroid insufficiency (CIRCI) to more fully describe the impairment of the HPA axis during critical illness. 7 CIRCI was defined as inadequate cellular corticosteroid activity for the severity of the patient's critical illness.…”
Section: Introductionmentioning
confidence: 99%